KONSEP PENDIDIKAN AKHLAK MENURUT IMAM AL MAWARDI DALAM KITAB ADAB AD-DUNNYA WA AD-DIN TERHADAP PERILAKU SISWA DI SMP MUHAMMADIYAH 06 DAU MALANG - Ani Lailaturrohmah; Muhammad Hanif; Ika Anggraheni (VICRATINA, 2021)
Moral education is responsible for the overall character formation in improving their identity. Student associations are getting worse day by day which leads to promiscuity, drinking, not knowing manners and juvenile delinquency that are rampant throughout the moral and religiosity order of the defendant. Moral education is necessary to fortify young people with the religious values of Islamic teachings. Religious values are not enough to be taught in the classroom which are knowledge only but must be applied in life. Moral education is an empowerment of the potential of the human mind to create good behavior in order to achieve complete happiness. Humans are multi-dimensional creatures. Not only because humans theologically have a sense and awareness to develop their patterns of life, but more than that, they also become objects in their overall activities and creativity. In conducting this research, the researcher used deductive qualitative research method. While the method used to collect data is through the essay of Shaykh Abu Hasan which is documented in his masterpiece, the book of adab Ad-Dunya wa Ad-Din. To analyze the data, the researcher uses a qualitative deductive analysis technique, which is to describe the existing data to describe the reality described in his book according to the actual phenomenon.